In Vitro Antitumor Active Gold(I) Triphenylphosphane Complexes Containing 7-Azaindoles - Štarha, Pavel; Trávníček, Zdeněk; Drahoš, Bohuslav; Dvořák, Zdeněk (International journal of molecular sciences, 2016)
A series of gold(I) complexes of the general composition [Au(naza)(PPh₃)] (1-8) was prepared and thoroughly characterized (e.g., electrospray ionization (ESI) mass spectrometry and multinuclear nuclear magnetic resonance (NMR) spectroscopy). The N1-deprotonated anions of 7-azaindole or its derivatives (naza) are coordinated to the metal centre through the N1 atom of their pyrrole ring, as proved by a single crystal X-ray analysis of the complexes [Au(3I5Braza)(PPh₃)] (7) and [Au(2Me4Claza)(PPh₃)]·½H₂O (8'). The in vitrocytotoxicity of the complexes 1-8 was studied against both the cisplatin-sensitive and -resistant variants of the A2780 human ovarian carcinoma cell line, as well as against the MRC-5 human normal fibroblast cell line. The complexes 4, 5, and 8, containing deprotonated 3-iodo-7-azaindole, 5-bromo-7-azaindole, and 2-methyl-4-chloro-7-azaindole (2Me4Claza), respectively, showed significantly higher potency (IC50 = 2.8-3.5 µM) than cisplatin (IC50 = 20.3 µM) against the A2780 cells and markedly lower effect towards the MRC-5 non-cancerous cells (IC50 = 26.0-29.2 µM), as compared with the mentioned A2780 cancer cells. The results of the flow cytometric studies of the A2780 cell cycle perturbations revealed a G₂-cell cycle phase arrest of the cells treated by the representative complexes 1 and 5, which is indicative of a different mechanism of action from cisplatin (induced S-cell cycle phase arrest). The stability of the representative complex 8 in the water-containing solution as well as its ability to interact with the reduced glutathione, cysteine and bovine serum albumin was also studied using ¹H and 31P-NMR spectroscopy (studied in the 50% DMF-d₇/50% D₂O mixture) and ESI+ mass spectrometry (studied in the 50% DMF/50% H₂O mixture); DMF = dimethylformamide. The obtained results are indicative for the release of the N-donor azaindole-based ligand in the presence of the used biomolecules.
Keywords: indoly; Humans; zlato; Indoles; gold(I) complexes; Cell Cycle; triphenylphosphane; buněčná smrt; Antineoplastic Agents; krystalografie rentgenová; fosfiny; Crystallography, X-Ray; lidé; crystal structures; antitumor activity; 7-azaindole; protonová magnetická rezonanční spektroskopie; voda; nádorové buněčné linie; protinádorové látky; in vitro; Water; Gold; Cell Line, Tumor; Phosphines; Proton Magnetic Resonance Spectroscopy; Cell Death; buněčný cyklus